Seasonal occurrence of Conopomorpha sinensis (Gracillariidae: Lepidoptera) infesting litchi (Litchi chinensis) in Himachal Pradesh - BHAT, ABHISHEK; RANA, V K; CHANDEL, V G S; SHANDIL, DEEPIKA; SAMAL, IPSITA (The Indian Journal of Agricultural Sciences, 2025)
Litchi fruit borer [Conopomorpha sinensis (Bradley)] is one of the biggest threats to litchi (Litchi chinensis Sonn.) farmers causing severe loss in fruit production. The present study was carried out during 2021 and 2022 at five different locations, viz. Regional Horticulture Research and Training Station, Jachh and Litchi Mango Research Station, Nagrota Bagwan, Kangra; Regional Horticulture and Forestry Research and Training Station, Bhota, Hamirpur; Progeny-cum- Demonstration Orchard, Nihari Bilaspur and Pingla, Mandi, Himachal Pradesh to determine the pattern and degree of infestation and its relationship to abiotic factors, a survey was conducted on incidence and seasonal occurrence of litchi fruit borer on different cultivars. During the survey, the mean infestation of the litchi fruit borer ranged from a minimum of 20.25% in Bhota of Hamirpur district to maximum 53.79% in Nagrota Bagwan, Kangra district. The average fruit infestation per cent was least in the Dehradun variety (17.50%) and maximum in the McLean variety (64%). However, study on seasonal incidence on pooled mean basis showed lowest fruit infestation (8.15%) in month of March and highest (47.00%) in month of July in Dehradun cultivar of litchi. Similarly, in case of Calcuttia cultivar infestation of fruit borer ranged from 12.67–53.67% from March to July, respectively. Infestation on late maturing variety Calcuttia was found to be more than that of Dehradun variety of litchi. Fruit infestation was non-significantly correlated with maximum relative humidity and temperature and minimum relative humidity whereas, was significantly and positively correlated with minimum temperature and rainfall in both varieties which shows that abiotic factors like rainfall play a significant role in borer infestation.